A Case Study on How Distance Education May Inform Post-Pandemic University Teaching - Mavroudi, Anna; Papanikolaou, Kyparisia (International Review of Research in Open and Distributed Learning, 2022)
Higher education recently found itself in the unprecedented situation of being forced to rapidly switch to online education as a demand of the COVID-19 pandemic. The aim of this article is to compare and contrast the experiences of university tutors who teach in two distance education universities with those who teach in a traditional university concerning their online lessons during lockdown. Forty university tutors participated in a survey to capture their teaching experiences. The survey was based on the transactional distance theory. Both qualitative and quantitative data were collected from both groups. Analysis of the quantitative data indicates no significant differences between the two groups in scores regarding course structure flexibility and the degree of student autonomy; however, significant difference with a high effect size was found regarding instructional dialogue, in favor of the distance tutors’ group. Thematically analyzing the qualitative data allowed the researchers to group the data into three main themes focused on how the instructional dialogue was manifested in the classes of both groups: (a) the learning design approach adopted, (b) the tutor-led interaction for student support, and (b) learner-to-learner communication and the sense of an online community. Ensuing recommendations involve adopting social-constructivist approaches that can sustain high-quality instructional dialogue in online learning settings and creating distance education faculty development programs in traditional universities that will help tutors support dialogical forms of online pedagogy.